Climate Change-Related Displacement and the Determination of Refugee Status under the 1951 Refugee Convention - Sritharan, Elijah S. (LeXonomica, 2023)
Climate change and climate-driven migration are two of the defining challenges of the twenty-first century, and there is no legal framework for protecting those displaced across national borders for climate-related reasons. The 1951 Refugee Convention hardly applies to human mobility in the context of climate change. This paper was written in the hopes of initiating a discussion concerning an alternative perspective through which persons fleeing natural disasters linked to climate change may satisfy the eligibility conditions for recognition of refugee status. Expanding the definition of refugee as defined in the Convention by including the notion of vulnerability to climate disasters that are caused by the underlying socio-economic conditions in the claimant’s home country and the role of discrimination in causing differential exposure to the climate-related disasters in legal definitions might open the door for the availability of refugee status for persons fleeing in the context of climate change. This paper proposes the adoption of a reformed human rights-based interpretation, particularly with regard to the individual nature of refugee status determination. Recalibrating the Convention to facilitate climate-induced migration could reduce political tension and social unrest in receiving countries.PovzetekPodnebne spremembe in migracije, ki jih povzroča podnebje, so eden od glavnih izzivov enaindvajsetega stoletja, vendar ni pravnega okvira za zaščito oseb, ki so zaradi podnebnih sprememb razseljene prek državnih meja. Konvencija o statusu beguncev iz leta 1951 se skorajda ne uporablja za mobilnost ljudi v okviru podnebnih sprememb. Ta dokument je bil napisan v upanju, da bo sprožil razpravo o alternativni perspektivi, s katero bi osebe, ki bežijo pred naravnimi nesrečami, povezanimi s podnebnimi spremembami, lahko izpolnile pogoje za priznanje statusa begunca. Razširitev opredelitve begunca, kot je opredeljena v Konvenciji, z vključitvijo pojma ranljivosti za podnebne nesreče, ki so posledica temeljnih družbenoekonomskih razmer v prosilčevi matični državi, in vloge diskriminacije pri povzročanju različne izpostavljenosti s podnebnimi nesrečami povezanim nesrečam v pravne opredelitve bi lahko odprla vrata za pridobitev statusa begunca za osebe, ki bežijo zaradi podnebnih sprememb. Ta dokument predlaga sprejetje reformirane razlage, ki temelji na človekovih pravicah, zlasti glede individualne narave določanja statusa begunca. Preoblikovanje Konvencije za olajšanje migracij, ki jih povzročajo podnebne spremembe, bi lahko zmanjšalo politične napetosti in socialne nemire v državah sprejema.
Keywords: climate change; climate-driven migration or displacement; climate migrants or refugees; determination of refugee status; the 1951 refugee convention; human rights-based approach; socio-economic conditions; vulnerability to climate disasters; the role of discrimination; rights-based climate litigation